BENTUK KETIDAKADILAN GENDER TERHADAP TOKOH PEREMPUAN DALAM FILM â7 ì 32 ì¼â (July 32nd): KAJIAN KRITIK SASTRA FEMINIS - , JESSICA N ELLISON, Cahyaningrum Dewojati, S.S., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
â7ì 32 ì¼(July 32nd)â movie tells about the life story of young women who sold to be courtesan. This film used as material object because the story is a representation of feminism. This study reveals of gender inequality issues toward woman that dominate this movie. This movie also represent about feminism ideas as the resistance of woman against gender inequity. To find gender inequity issues toward woman that dominate this movie, dialogue analyzing and woman and man characters to be separated as pro feminism or contra feminism identification are needed. The pro feminism characters are Kkotnim, Lee Mansu, and Dong Wook. While the contra feminism characters are Inspector Jang and Ajimae. This movie reveals several gender inequity issues such as violence against woman and stereotype against woman. The violence against woman in this movie separated into four cases. First, time work inequity, early age prostitution, prostitution causes sexual harassment, and prostitution cause physical harassment. While stereotype against woman in this movie separated into three cases. They are women are holders of domestic matters, woman dependency toward man, and all courtesan are revolt. The raising of feminism ideas as woman inequality resistances in this movie are resistance woman depends to man, violence resintance, and woman has right to be free from man dominations.